The national research council's rankings of doctoral programs in public affairs - Morcol, Goktug; Han, Sehee (2018)
Using the National Research Council (NRC) data, this study aimed to answer two questions: What are the factors that contributed the most to the rankings of public affairs programs? Are there more specific patterns in the rankings of the doctoral programs in public affairs? The results indicate that faculty research productivity is the most important predictor of the rankings of the doctoral programs in the NRC dataset. The results of cluster analyses show that there are programs at large public universities, which are ranked highly and have highly diverse faculty and students. - Reproduced.
Keywords: Doctoral education; Public administration - Research